Genetics and molecular mapping of gynoecious (F) locus in cucumber (Cucumis sativus L.). Issue 1 (2nd January 2019) - Jat, Gograj Singh; Munshi, Anilabh Das; Behera, Tusar Kanti; Choudhary, Harshwardhan; Dash, Prasanta; Ravindran, Amarnath; Kumari, Shilpi
ABSTRACT: Gynoecious is an important economic trait of cucumber for determinant of earliness and yield, yet genetic mechanism is not well understood for this trait. The experiment was conducted using F2 mapping population by crossing of PPC-2, a gynoecious and parthenocarpic line with Pusa Uday (monoecious and non-parthenocarpic cultivar). Out of 179 SSR markers screened, 39 markers differentiated the gynoecious and monoecious parents. However, only 17 markers were segregating with F2 mapping population, those were used for genotyping and linkage map analysis and these markers were placed along with F locus on chromosome 6 covering a total distance of 100.4cM. The SSR markers, SSR13251 and UW020605 were found to be closely linked to gynoecious ( F ) locus at 1.0 and 4.5 cM, respectively. The segregation of F2 population of PPC-2 × Pusa Uday and GPC-1 × Punjab Naveen and test crosses for sex type herein suggested that single dominant gene controlled the gynoecious sex expression in cucumber particularly in gynoecious genotypes PPC-2 and GPC-1. Therefore, the monogenic dominant nature of gynoecious sex identified in the present experiment and SSR markers closely linked to the F locus will be useful in marker-assisted backcross breeding for transfering gynoecious trait into horticulturally desirable varieties.